ABOLITION OF POLYGAMY IN TURKIYE: JURIDICAL STUDY OF KEMALIST REFORM - Jufrizal, Jufrizal; Sulfinadia, Hamda; Efrinaldi, Efrinaldi (University of Islam Malang, 2025)
This study aims to examine the historical and legal transformation of polygamy regulation in Turkiye, from its initial permissibility to its eventual prohibition under the influence of Kemalist secular reforms. With information acquired from documentation and library research, this study employs a juridical-normative approach and a qualitative-descriptive method. The findings indicate that the abolition of the 1917 Ottoman Family Law resulted in the unequivocal prohibition of polygamy, which had been permitted under certain situations, with the enactment of the Turkish Civil Code by Mustafa Kemal Atatürk. The study highlights the significant role of Kemalism in shaping the legal landscape of Turkiye, particularly in transitioning from religious to secular legal frameworks. While the research offers important insights into the intersection of law, secularism, and social reform, it is limited by its reliance on secondary sources and the absence of field-based empirical data. Nevertheless, it contributes to the broader discourse on legal modernization and the socio-political implications of secularism in Muslim-majority societies.